2007
DOI: 10.1007/bf02977606
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of cleomiscosins A and C isolated fromAcer okamotoanum

Abstract: Phytochemical investigation of Acer okamotoanum leaf and twig led to the isolation of two coumarinolignans, cleomiscosin A (1) and cleomiscosin C (2). Here, we found that 2 dose-dependently inhibits LDL oxidation mediated by either catalytic copper ions (Cu2+) or free radicals generated with the azo compound 2,2'-azobis-(2-amidinopropane)dihydro-chloride (AAPH) with IC50s of 29.5 and 11.9 microM, respectively. By electrophoretic analysis, we also observed that 2 protects apolipoprotein B-100 (apoB-100) against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Previous studies have reported that the seeds of C. icosandra contain coumarino-lignans such as cleomiscosin A, B, C and D, of which A and C are reported to be antioxidants [16,35]. Collectively, these observations indicate that the free radical scavenging potential of C. icosandra seeds and protection they confer against oxidative DNA damage may be attributed to their phytochemical composition.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have reported that the seeds of C. icosandra contain coumarino-lignans such as cleomiscosin A, B, C and D, of which A and C are reported to be antioxidants [16,35]. Collectively, these observations indicate that the free radical scavenging potential of C. icosandra seeds and protection they confer against oxidative DNA damage may be attributed to their phytochemical composition.…”
Section: Discussionmentioning
confidence: 79%
“…Concerning the relative configuration of 1, the trans-diaxial arrangement of H-7 and H-8 in the benzodioxan is in conformity with the large coupling constant of 8.0 Hz between the two vicinal oxymethine protons (Jin et al, 2007). In addition, two coumarinolignan compounds, named cleomiscosins A and C, have been isolated from Cleome viscosa seeds and their stereochemistry at C-7 and C-8 showed several common features with 1 by comparison with their 1 H-and 13 C-NMR shifts (Ray et al, 1985).…”
Section: Resultsmentioning
confidence: 84%
“…Mohsen Chiani 1 | Mohammad Ali Shokrgozar 2 | Kayhan Azadmanesh 3 | Dariush Norouzian 1 | Mohammad Reza Mehrabi 1 | Aazam Najmafshar 4 | Azim Akbarzadeh 1 1 | INTRODUCTION Bleomycin (BLM) is an antitumor antibiotic commonly used in treatment of several types of cancer. [1][2][3][4][5] Bleomycin is known to induce single, and to some extent, double-stranded breaks in DNA. In several studies, bleomycin has been shown to cause cell cycle arrest in G2 and in mitosis.…”
Section: Preparation Characterization and In Vitro Evaluation Of Blmentioning
confidence: 99%